HUMAN MOTORICS SCIENCE OR FIELD OF INTERVENTION? (Fiep Bulletin - online, 2014)
The text seeks to identify the present condition of what is still called the 'Physical Education', which still lacks a specific and scientifically proven theory to sustain it. It emphasises that even when developed within the university, it must be reviewed and better identified with the minimal requisites for academically develop a given area, academic subject or career, as an area descending from investigation and having a technical-scientific vocabulary, and not merely the structuring of practice. In the text, a few terms used by professionals of the area, such as Human Movement, Kinesiology, Sports Science, Human Motorics and Physical Activity, are analysed, with the concepts usually presented. Following some theoretical and epistemological treatment applied to the terms just mentioned, the author closes declaring that Human Motorics is, for him, the scientific knowledge which serves as a ground and occupies itself with that academic area - Physical Education - representing also a field of intense and wide professional intervention.
Keywords: Human Motorics; Science; Professional Intervention Field